Experiencing weight stigma during childbirth increases the odds of cesarean birth - Regula A. Schwenk; Carmen Wyss; Evelyne M. Aubry (BMC Pregnancy and Childbirth)
Abstract Background Weight-biased clinical practices and institutional characteristics can have a wide impact on the quality of care provided to women with obesity. This may substantially increase their risks for poor birth outcomes. The current study assessed experienced weight stigma by women during childbirth in maternity care settings in Switzerland. We aimed to identify frequencies, sources, and manifestations of weight-related stigmatization, hypothesizing that such stigma impacts birth outcomes, specifically cesarean birth (CB). Methods Data from a nationwide cross-sectional online survey was used to investigate the frequencies, sources, and manifestations of experienced weight stigma during childbirth. Binomial logistic regression was applied to predict CB from experienced weight stigma. Mediation analysis assessed the role of experienced weight stigma in the association between body mass index (BMI) and CB. Results In a total of 1352 women who gave birth in the last five years, women with obesity (BMI ≥ 30 kg/m2) experienced weight stigma more often than their peers with healthy weight (BMI 18.5–24.9 kg/m2). Obstetricians were identified as a major source of weight stigma, accounting for 77.8% of stigmatization experienced by women, compared to stigmatization perceived from nurses (21.7%) and midwives (23.8%). Overall, weight stigma was mostly experienced in the form of dismissive or critical comments towards a woman’s figure or weight. Significantly more women with obesity indicated being blamed for weight-related risks during childbirth than their healthy-weighted peers (χ²(2) = 22.2, P < 0.001). An increase in the frequency of experienced weight stigma was related to higher odds of intrapartum CB ([aOR], 1.08; 95% CI, 1.02,1.15; P < 0.05), and it partially mediated the relationship between increased pre-pregnancy BMI and CB (b = 0.07, SE = 0.029; P < 0.05). Conclusion Women with obesity reported the highest proportion of weight stigmatization during childbirth, experiencing stigma more frequently than women without obesity. This increased frequency of weight stigma was associated with higher odds of CB. Raising awareness among healthcare providers and reducing potential biases and stigmatization may improve care quality and health outcomes for women with obesity.